NILAI-NILAI KEMANUSIAAN YANG MELINTAS BATAS KEAGAMAAN DALAM NARASI ORANG SAMARIA YANG BAIK HATI - Joseph Christ Santo (Sekolah Tinggi Teologi Arastamar Bengkulu, 2024)
The narrative of the Good Samaritan as written in the Gospel of Luke is a familiar narrative among Christians. Some researchers have raised this narrative in terms of ethnic differences, but researchers are interested in examining this narrative from another point of view, namely religious differences. The dispute between the Jews and the Samaritans implied in this narrative is not only due to ethnic differences but also to religious differences. One of the religious conflicts that has occurred before is the imposition of Judaism on the Samaritans that occurred in Hyrcanus' time. Using a descriptive analysis approach, the researcher came to the conclusion that the narrative contains human values in terms of equality, compassion, and totality.